The Use of CFD for Investigating Fluidelastic Instability in Tube Arrays - Sanches, Rafael Adriano Kuche (Trinity College Dublin. School of Engineering. Mechanical & Manufacturing Engineering, 2007)
There are several applications of tube arrays subject to cross flow in the industry, mostly for heat exchanging. These tubes are subject to forces arising due to the flow, and under certain conditions they can experience large amplitude self exited vibration, phenomenon named Fluidelastic Instability (FEI), a potentially catastrophic phenomenon when occurring in structures dimensioned for static loads. Through this work a brief review of the different methods of modelling FEI is presented, and the use of the commercial Computational Fluid Dynamics (CFD) solver FLUENT to predict the forces acting in a tube of an array subject to cross flow is analyzed. A few experiments are performed in order to compare the simulation results to real data. Finally, the Reynolds Stress Model (RSM) is found to provide better results, but still not very faithful to the reality. Guidelines for preparation of a good simulation of flow through a tube array, mesh construction and turbulent models are presented. A comparison between results from several turbulent models is presented. The most appropriate model is then chosen and more results are presented. Future work is pointed to simulation with dynamic mesh and to a methodology of adaptation of CFD results for quasi steady fluidelastic instability model.
Keywords: fluidelastic instability; tube array; CFD; fluid forces; flow induced vibration; quasi-steady